EFFECTS OF TRADITIONAL MUSIC THERAPY ON EMOTION REGULATION OF EARLY CHILDHOOD IN A SCHOOL ENVIRONMENT - Miftahul Jannah; Hasrat A Aimang (JURNAL PENDIDIKAN GLASSER, 2025)
This study aimed to explore the effects of traditional music therapy on early childhood emotion regulation in a school setting, specifically at Al Hasanah Luwuk Kindergarten. The study participants consisted of 30 randomly selected children. The research method used a quasi-experimental approach with a pre-test and post-test design. The children were given traditional music therapy sessions for 8 weeks, with a frequency of twice per week. The results showed a significant improvement in children's emotion regulation ability after attending traditional music therapy. Data analysis was conducted using t-test for paired samples, which showed that the mean value of the post-test was higher than the pre-test with p<0.05. The findings suggest that traditional music therapy can be an effective intervention in improving early childhood emotion regulation. The implication of this study is the importance of integrating local cultural elements in school learning programs to support children's emotional development.